The biological role of extracellular vesicles in gastric cancer metastasis - Lei, Yun; Cai, Shuang; Zhang, Chun-Dong; Li, Yong-Shuang (Frontiers in Cell and Developmental Biology, 2024)
Gastric cancer (GC) is a tumor characterized by high incidence and mortality, with metastasis being the primary cause of poor prognosis. Extracellular vesicles (EVs) are an important intercellular communication medium. They contain bioactive substances such as proteins, nucleic acids, and lipids. EVs play a crucial biological role in the process of GC metastasis. Through mechanisms such as remodeling the tumor microenvironment (TME), immune suppression, promoting angiogenesis, and facilitating epithelialmesenchymal transition (EMT) and mesothelial-mesenchymal transition (MMT), EVs promote invasion and metastasis in GC. Further exploration of the biological roles of EVs will contribute to our understanding of the mechanisms underlying GC metastasis and may provide novel targets and strategies for the diagnosis and treatment of GC. In this review, we summarize the mechanisms by which EVs influence GC metastasis from four aspects: remodeling the TME, modulating the immune system, influencing angiogenesis, and modulating the processes of EMT and MMT. Finally, we briefly summarized the organotropism of GC metastasis as well as the potential and limitations of EVs in GC.